Continuous Intravenous Lidocaine for Acute Pain Management Post Laparotomy Surgery: A Case Series - Sri Wahyuningsih; Charles Wijaya (Journal of Anesthesiology and Clinical Research, 2023)
Introduction: Acute post-operative pain can lead to prolonged use of opioids and progress to chronic pain. Multimodal analgesic approaches have replaced the use of opioid monotherapy, but opioid use continues and contributes to inadequate acute pain management. Intravenous lidocaine has analgesic, anti-hyperalgesic, and anti-inflammatory effects. This study aims to describe post-operative pain management using intravenous lidocaine. Case presentation: There were two cases. The first was a 32-year-old female patient with suspected interrupted ectopic pregnancy who underwent emergency laparotomy under spinal anesthesia and, after 2 hours, was converted to general anesthesia. Postoperatively, the analgesic lidocaine was given as a 52 mg intravenous bolus followed by a continuous 36 mg/hour/syringe pump. The patient's VAS scale was initially 2/10, and on the third day, 1/10 continued treatment. In the second case, an 18-year-old male patient with suspected acute appendicitis underwent a midline incision laparotomy appendectomy with spinal anesthesia. Postoperatively, lidocaine was given a slow bolus of 75 mg intravenously, finished in 5 minutes, then 50 mg/hour/intravenously. The patient's VAS scale was initially 2-3/10 until on the third day. He was transferred to a room with a VAS of 1-2/10. Conclusion: Lidocaine is an effective intravenous analgesic to treat acute pain after laparotomy surgery. Administration of relatively low doses can achieve post-operative analgesia without concern for toxicity.